A case of eosinophilic pustular folliculitis presenting as papuloerythroderma of Ofuji‐like eruption. Issue 2 (2nd December 2020) - Maekawa, Aya; Nakagawa, Yukinobu; Kakuda, Kasumi; Kiyohara, Eiji; Wataya‐Kaneda, Mari; Fujimoto, Manabu
Abstract : We report a case of eosinophilic pustular folliculitis which showed pruritic erythroderma‐like eruption with deck‐chair sign, peripheral eosinophilia and elevated serum levels of IgE and TARC, mimicking papuloerythroderma of Ofuji.